How Traditional Production Shapes Perceptions of Product Quality - Wilcox, Keith; Laporte, Sandra; Ward, Gabriel (Journal of Consumer Research, 2024)
Abstract The current research examines how the knowledge that a product is made using a traditional method influences perceptions of its quality. We propose that consumers believe that a brand using traditional methods is beneficial for society because it is concerned about cultural preservation and this belief has a positive effect on perceived quality. Six experimental studies show that consumers evaluate products produced with a method described as traditional to be higher in quality than similar products that are not described as traditionally made and this effect is mediated by the belief that the brand is beneficial for society. Consistent with this theory, the positive effect of traditional production on perceived quality is attenuated when consumers view the brand to be unconcerned about cultural preservation, such as when the use of a traditional method is framed as a follower strategy (i.e., it imitates the actions of other brands) or when the brand is a multinational company. By showing that the mere mention of a traditional method can be another subtle way to position a brand as a moral actor, these findings contribute to the understanding of the link between perceived social responsibility and product evaluations.